Conectando la educación matemática infantil y el pensamiento computacional: aprendizaje de patrones de repetición con el robot educativo programable Cubetto® (Innovaciones Educativas, 2022)
In recent years, the links between mathematics education and computational thinking have been strengthening since both share various skills around problem-solving; however, early childhood teachers have had little training to implement activities that promote this thinking in the mathematics classroom. In this sense, this article aims to investigate the connections between early childhood mathematics education and computational thinking so that early childhood teachers can design and implement activities that allow them to develop skills in these two types of thinking in an integrated manner. Towards achieving this purpose, an experience of learning repetition patterns through the Cubetto programmable educational robot is described and analyzed. The activity is implemented with 24 5-year-old children from a public school in Girona (Spain), and the results show that an essential part of the 5-year-old children represents the pattern correctly (62.5%), being the graphical representation the most common among the participants who solve the tasks correctly (86.7%). It is concluded that, in the current context, it is necessary to continue designing activities that promote the development of mathematical knowledge playfully through teaching management based on skills such as problem-solving, reasoning, communication, connections, and representation while also developing digital skills and logical and computational thinking.
Keywords: early childhood mathematics education; patterns; computational thinking; programmable educational robot; teaching practices; Education